Experiential Learning and Research for Undergraduates in Public Health: Transferring Focus Group Research to Peer Reviewed Journal Publication and Public Health Practice - Susi Keefe; Michelle Gin (Hmong Studies Journal, 2020)
University collaboration with public health agencies is a proven effective way to connect students and faculty to real world local public health problems (Neri et al., 2014; Greece et al., 2018). An undergraduate capstone Senior Seminar course worked with a Minnesota state agency and community initiative, the Mercury in Skin Lightening Products Workgroup to address the use of toxic skin lightening products in Minnesota. Students conducted focus group research with Hmong college students in St. Paul, MN on the topic of skin lightening products. Since the end of the course, six students wrote a research paper that was accepted for publication in a peer reviewed journal and applied their knowledge into public health practice (Keefe et al., 2018). This article explores the high impact of courses with community and agency collaborations with emphasis on the potential to publish findings from research with undergraduates.